Saving Grace [large type] - Green, Jane, 1968- (Wheeler Publishing, 2014)
Grace and Ted Chapman. Literary power couple. Ted is considered "the thinking man's John Grisham" and Grace, his wife of twenty years is beautiful, stylish, carefree. All of this is on the surface. Beneath, what no one sees, is Ted's rages. His mood swings. And the precarious house of cards that their lifestyle is built upon. When Ted's longtime assistant and mainstay leaves, the house of cards begins to crumble and Grace, with dark secrets in her past, is most vulnerable. To the rescue comes Beth, a new assistant. Someone who will help handle Ted. Someone who has the calm efficiency to weather the storms that threaten to engulf their household. Soon, though, it's clear to Grace that Beth might be too good to be true. And that this new interloper might be the biggest threat of all, one that could cost Grace her marriage, her reputation, and even her sanity.